Desain, Jenis dan Metode Dalam Penelitian Kualitatif - Anggriani, Bungaria; Azura, Dinda Siti; Muhaimin, Imanuddin; Khairani, Candy (Komprehensif, 2025)
Qualitative research provides deep insights into the context and meaning of human behavior through a flexible approach. Various designs, such as case studies, phenomenology, and ethnography, are outlined to demonstrate their respective advantages. Data collection methods, including in-depth interviews, observations, and document analysis, are introduced to explore rich and diverse information. This research shows that the selection of appropriate designs and methods significantly impacts research outcomes.